Iron-carbon modified zirconium oxide composite photocatalyst as well as preparation method and application thereof
By modifying ZrO2 with iron carbon and adding Fe3O4 and CQDs to form a composite photocatalyst, the problems of low efficiency and insufficient stability of glyphosate wastewater treatment in the prior art are solved, and efficient glyphosate degradation and recycling of photocatalysts are achieved.
Patent Information
- Application Number
- CN202411944047.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art has problems of low efficiency and insufficient stability when treating glyphosate wastewater, especially the wide band gap, low light response, and slow electron-hole pair generation rate of ZrO2.
By iron-carbon modification of ZrO2, Fe3O4 and carbon quantum dots (CQDs) are added to form a composite photocatalyst for iron-carbon modification of zirconia. The composite material extends the photoresponse range through Fe3O4, and CQDs inhibit the separation of photogenerated electrons and holes, extend the lifetime of interface carriers, and achieves coordinated adsorption/photocatalytic degradation of glyphosate.
The photocatalytic degradation efficiency of glyphosate is significantly improved, the stability of the photocatalyst is extended, and the efficient recovery of phosphorus and the recycling of photocatalysts are achieved.
Smart Images

Figure CN119771408A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wastewater treatment, and in particular to an iron-carbon modified zirconium oxide composite photocatalyst and a preparation method and application thereof. Background Art
[0002] Glyphosate (C3H8O5P) is the active ingredient in glyphosate-based herbicides (GBHs). It is widely used in agricultural and non-agricultural fields to control annual and perennial weeds and is also considered one of the herbicides with the greatest risk to human health. Glyphosate is usually applied in high and low concentrations in conventional agriculture, before and after the planting of conventional crops. In addition, glyphosate is also used to control invasive vegetation in forestry, algae proliferation in aquaculture, and invasive weeds around perennial trees. As a result, the global use of GBHs has increased significantly, from 56,296 tons in 1994 to 825,804 tons in 2014, and is expected to reach 7.4-9.2 million tons by 2025. The increasing use of glyphosate worldwide has raised concerns about its persistence in water sources, non-target plants, and the environment. The human body absorbs the residues through ingestion, inhalation, and skin contact. Some studies have evaluated the effects of glyphosate exposure on the nervous system and found that it can cross and affect the blood-brain barrier and cause various types of short-term or long-term disorders in the human nervous system. In addition to causing damage to the human body, glyphosate residues also have certain effects on plants and animals. In summary, glyphosate can cause harm to the ecological environment and human health, so it is crucial to effectively treat glyphosate wastewater.
[0003] In order to eliminate the threat of glyphosate to biological health, some progress has been made in the degradation of glyphosate. The main removal methods currently include physical, biological and chemical methods. Photocatalysis, as one of the chemical methods, is a promising technology. The main advantages of using photocatalysis are simple structure, easy handling, high productivity and environmental friendliness. Heterogeneous photocatalysis includes the following processes: (1) The reactants are adsorbed on the catalytic center of the photocatalyst surface; (2) When the photon energy is greater than the band gap, the photon causes the photocatalyst surface to generate electrons and "excite" them in the valence band, causing them to migrate to the conduction band, resulting in the formation of holes in the valence band; (3) The photogenerated electrons and holes are transferred to the photocatalyst surface and reach the catalytic center to undergo redox reactions with the pollutants; (4) The photogenerated electrons and holes can also react with O2 and H2O (or OH) to form electrons. - ) contact produces reactive oxygen species, including free radicals (i.e., superoxide radicals •O- 2 and •OH) and non-free radicals (i.e., singlet oxygen 1 O2), undergoes redox reaction with pollutants; (6) desorption process of the final product.
[0004] Semiconductors commonly used in photocatalysis are metal oxides, including ZnO, TiO2, WO3 and Fe2O3. To improve photocatalytic activity, metal oxides usually appear in a modified form rather than their original structure. ZrO2 has good dispersibility, stability and low toxicity, and has a high affinity for glyphosate, which can accelerate the contact between glyphosate and catalytic active sites and shorten the transmission path of photogenerated electrons and holes. However, ZrO2 has problems such as wide band gap, low photoresponse, slow electron-hole pair generation rate and fast recombination rate. Therefore, it is necessary to reasonably dope and modify ZrO2, shorten the transmission path of photogenerated electrons and holes, promote the separation of photogenerated electrons and holes, prolong the lifetime of interface carriers, build a more efficient photocatalytic degradation system, and achieve synergistic adsorption / photocatalytic degradation of glyphosate.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In order to address the deficiencies of the prior art, one of the objectives of the present invention is to provide an iron-carbon modified zirconia composite photocatalyst, which can achieve synergistic adsorption / photocatalytic degradation of glyphosate; and the composite material has good stability and reusability.
[0007] A second object of the present invention is to provide a method for preparing the above-mentioned iron-carbon modified zirconia composite photocatalyst.
[0008] The third object of the present invention is to provide an application of the above-mentioned iron-carbon modified zirconia composite photocatalyst.
[0009] A fourth object of the present invention is to provide a glyphosate degradation agent whose active component includes the above-mentioned iron-carbon modified zirconium oxide composite photocatalyst.
[0010] This application can be implemented as follows: In a first aspect, the present application provides a composite photocatalyst of iron-carbon modified zirconia, which comprises zirconia and Fe3O4 and carbon quantum dots (CQDs) for modifying zirconia; In an optional embodiment, the zirconium oxide material includes at least one of a monoclinic ZrO2 material, a tetragonal ZrO2 material, a monoclinic / tetragonal mixed ZrO2 material, a cubic ZrO2 material, and an amorphous ZrO2 material.
[0011] In an optional embodiment, the biomass for preparing CQDs includes at least one of soybean straw biomass, peanut shell biomass and pistachio shell biomass.
[0012] In an optional embodiment, the composite material has at least one of the following characteristics: Feature (1): The composite material has no obvious agglomeration phenomenon and the pore size between particles is small; Feature (2): Fine CQDs round particles are evenly distributed on the surface of the composite material; Feature (3): The pore size of the composite material is mostly between 1 and 5 nm; Feature (4): The composite material has a high specific surface area and a slit-like mesoporous structure.
[0013] In an optional embodiment, the molar ratio of Fe to Zr in the composite material includes 1:0, 0:1, 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, 0.4:1.
[0014] In an alternative embodiment, the CQDs and Fe 0.1 The molar ratio of Zr includes 1:0, 0:1, 0.01:1, 0.03:1, 0.05:1, 0.1:1, and 0.15:1.
[0015] In a second aspect, the present application provides a method for preparing a composite photocatalyst of iron-carbon modified zirconia as in any of the aforementioned embodiments, comprising the following steps: preparing ZrO2 of different crystalline phases, preparing FeZr composite materials, and preparing CFeZr composite materials.
[0016] In an optional embodiment, the preparation of ZrO2 with different crystalline phases includes: monoclinic ZrO2, tetragonal ZrO2, monoclinic / tetragonal mixed ZrO2, cubic ZrO2, and amorphous ZrO2.
[0017] In an optional embodiment, the preparation of the FeZr composite material includes: adding ZrO2 and Fe3O4 to a mixed solvent of deionized water and ethanol and ultrasonicating, removing the supernatant by centrifugation after the ultrasonication, and drying the obtained precipitate to obtain the composite material.
[0018] In an optional embodiment, the CFeZr composite material includes CQDs, and the preparation of the CQDs includes: pyrolyzing biomass.
[0019] In an optional embodiment, the pyrolysis temperature is 500-600°C; and the pyrolysis time is not less than 2h.
[0020] In an optional embodiment, the biomass is further dried and crushed before pyrolysis.
[0021] In a third aspect, the present application provides an application of a composite photocatalyst of iron-carbon modified zirconia according to any of the aforementioned embodiments, wherein the composite photocatalyst is used to degrade glyphosate.
[0022] In an alternative embodiment, the composite material is used to remove glyphosate.
[0023] The beneficial effects of this application include: The present application uses Fe3O4 and CQDs to co-dope ZrO2, wherein ZrO2 has a strong adsorption effect on glyphosate, which can shorten the transmission path of photogenerated electrons and holes; Fe can extend the light response range and further increase the oxygen vacancies (Ovs) in the material, promoting the separation of photogenerated electrons and holes; and the doping of CQDs can inhibit the separation of photogenerated electrons and holes and prolong the lifetime of interface carriers.
[0024] The ZrO2, Fe and CQDs in the composite photocatalyst can play a synergistic promotion effect by generating 1 O2、H + and •O- 2 to achieve efficient oxidative degradation of glyphosate and efficient adsorption and removal of the reaction product phosphate; at the same time, the composite material exhibited good stability during the reaction, achieving efficient recovery of phosphorus and recycling of the photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 is a scanning electron microscope image of each sample in Example 1; Figure 2 TEM images of the samples in Example 1; Figure 3 N2 adsorption-desorption isotherms and pore size distribution diagrams of each sample in Example 1; Figure 4 is the X-ray diffraction pattern of each sample in Example 1; Figure 5 is the Fourier transform infrared spectra of each sample in Example 1; Figure 6 It is the Raman spectrum of each sample in Example 1; Figure 7 The UV-visible diffuse reflectance spectra and band gap diagrams of the samples in Example 1; Figure 8 : is the photocurrent response diagram of each sample in Example 1; Fig. 9 is the photoluminescence emission spectrum of each sample in Example 1; Fig.10 is the electrochemical impedance spectrum of each sample in Example 1; Fig.11This is a diagram showing the effect of different crystal forms of ZrO2 on glyphosate removal in Experimental Example 2; Fig.12 This is a graph showing the effect of the molar ratio of Fe to ZrO2 on the removal effect of glyphosate by the FeZr composite material in Experimental Example 2; Fig.13 The CQDs prepared from different biomass in Experimental Example 2 have a significant effect on C 0.05 Fe 0.1 Comparison of the removal effect of Zr composite materials on glyphosate; Fig.14 CQDs and Fe in Experiment 2 0.1 The molar ratio of Zr to CFe 0.1 Effect of Zr composite materials on glyphosate removal; Fig.15 The degradation effects of different reaction systems on glyphosate and the kinetic curves in Experimental Example 3 are shown; Fig.16 C in Test Example 3 0.05 Fe 0.1 Figure 1. Experimental diagram of recycling of Zr composite materials. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0028] The following is a detailed description of the composite photocatalyst of iron-carbon modified zirconium oxide provided in the present application, as well as its preparation method and application.
[0029] The present application proposes a composite photocatalyst of iron-carbon modified zirconium oxide, which comprises zirconium oxide and Fe3O4 and CQDs doped therein; In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Example 1 This example prepares a composite photocatalyst of iron-carbon modified zirconium oxide, and the specific process is as follows: (1) Synthesis of ZrO2 material: Add 0.5 mL of zirconium n-butoxide to 10 mL of 30% H2O2 solution, stir at 180 rpm for 30 min at 25 ˚C, then add 30 mL of deionized water and continue stirring for 24 h. Transfer the above solution to a 100 mL Teflon autoclave, add deionized water to the volume of the solution to 100 mL, and keep it at 180 ˚C for 1 h; after the autoclave is cooled to room temperature, wash the composite material with deionized water and ethanol, and dry it at 60 ˚C for 12 h.
[0031] 2) Preparation of Fe3O4 / ZrO2 (FeZr) composite material: ZrO2 and Fe3O4 were added to a mixed solvent of deionized water and ethanol (v / v, 1 / 1) and ultrasonicated for 2 h. After the ultrasonication, the supernatant was removed by centrifugation. The obtained precipitate was dried in a vacuum oven at 60°C for 12 h to obtain Fe 0.1 Zr composite materials.
[0032] (3) Preparation of CFeZr composite materials: First, the waste biomass was washed with deionized water and dried in a drying oven at 105°C. The dried material was then cut into 1 cm pieces. The pretreated biomass was placed in a crucible and placed in a muffle furnace for pyrolysis. The chamber temperature was set at 5 ˚C / min. -1 The temperature was raised to 500°C and maintained for 2 h. After cooling to room temperature, the prepared biomass was ground to 80 mesh. 0.1 Zr and biomass were added to 10.0 mL of ethanol and ultrasonically dispersed for 30 min. The suspension was dried at 60 °C for 12 h to obtain C 0.05 Fe 0.1 Zr composite materials.
[0033] ①Sample characterization analysis: The samples of ZrO2, Fe 0.1 Zr and C 0.05 Fe 0.1 Zr was characterized and analyzed.
[0034] SEM analysis results ( Figure 1 ) showed that ZrO2 is composed of irregularly shaped small particles, and the slit-like porous structure formed is conducive to the adsorption and diffusion of glyphosate molecules, thereby improving the photocatalytic reaction rate; Fe after loading 0.1Some large particles with smooth surfaces appeared in the Zr composite material, and there was a certain agglomeration phenomenon, which led to an increase in pore size. 0.1 The agglomeration phenomenon of Zr composites is improved and the pore size between particles is reduced.
[0035] TEM analysis results ( Figure 2 ) shows that the particles of ZrO2 are small and evenly dispersed, indicating that it has a high specific surface area and can provide active catalytic sites. Fe is mainly combined with ZrO2 in the form of round particles with a diameter of about 50 nm; small round particles CQDs with a diameter of <10 nm appear on the surface of the material, as shown by tiny spheres and black dots, and the CQDs are highly dispersed without aggregation, indicating that the CQDs are evenly anchored on the Fe 0.1 Zr surface and successfully with Fe 0.1 Zr hybridization.
[0036] BET analysis results ( Figure 3 ) shows that ZrO2, Fe 0.1 Zr and C 0.05 Fe 0.1 The adsorption and desorption curves of Zr are consistent with the characteristics of the "IV" type isotherm, and the adsorption and desorption curves have a high degree of overlap and no obvious hysteresis loop, indicating that the sample has a high specific surface area and a slit-like mesoporous structure. 0.05 Fe 0.1 The specific surface area and pore volume of Zr composites are higher than those of Fe 0.1 Zr increased slightly, and the average pore size remained basically unchanged, indicating that CQDs increased Fe 0.1 The dispersion of Zr composites is improved and the number of reaction sites in the composites is expanded.
[0037] XRD analysis results ( Figure 4 ) showed that Fe successfully replaced part of the ZrO2 lattice to form Fe 0.1 Zr composites, CQDs were also successfully loaded on Fe 0.1 In Zr material, the results are consistent with those of SEM and TEM.
[0038] FTIR analysis results ( Figure 5 ) shows that ZrO2 at 1454 cm -1 The adsorption peak at 478 cm is the deformation oscillation peak of Zr-OH. The Zr-OH adsorption site generated by ligand loss is conducive to the selective adsorption of glyphosate. -1 The absorption peak at corresponds to the stretching vibration of the Zr-O-Zr bond, confirming the successful preparation of ZrO2; 0.1 In the hybrid spectrum of Zr composite materials, 500 cm -1The Fe-O stretching vibration absorption peak on the left and right may be covered by the Zr-O-Zr absorption peak, which manifests as a change in wavelength and bandwidth.
[0039] Raman analysis results ( Figure 6 ) verified the amorphous phase characteristics of ZrO2 in the sample, and the emergence of the new band indicated that Fe was successfully loaded on ZrO2, which helped to improve the photocatalytic activity of the composite material.
[0040] ②Optical and electrochemical performance analysis: The optical and electrochemical properties of the samples were analyzed by ultraviolet-visible diffuse reflectance (UV-vis DRS), photocurrent response (IT test), photoluminescence emission spectroscopy (PL), electrochemical impedance spectroscopy (EIS), and time-resolved fluorescence decay spectroscopy (TR-PL).
[0041] Figure 7 The UV-vis DRS spectra and band gap diagrams of the samples are shown. 0.1 In Zr composites, Fe introduces an additional energy level between VB and CB of ZrO2, and the dd transition caused by the charge transfer of different Fe ions ( 2 T 2g / 2 A 2g or 2 T 1g ), which reduces the optical band gap; and the overlap of the defect state caused by OVs and the semiconductor band edge will also reduce the band gap of the composite material. 0.05 Fe 0.1 The Zr band gap is further reduced due to the integration of CQDs which improves the charge mobility, optimizes the electronic structure, and reduces the band gap width, thereby enhancing the photocatalytic activity.
[0042] Figure 8 The IT test analysis results of the samples are displayed. The introduction of Fe and CQDs can improve the carrier separation efficiency. Both can make the composite material have wider light absorption and higher light capture efficiency, thereby improving the photoelectric conversion efficiency. At the same time, it can also promote the separation and migration of electron-hole pairs and increase the photocurrent density.
[0043] Fig. 9 The PL analysis results of the samples are shown. The interface coupling formed after pure ZrO2 is doped with Fe can effectively extract electrons and significantly inhibit the recombination of photogenerated electron pairs. 0.05 Fe 0.1 The photoluminescence intensity in the Zr composite material is further reduced, which may be due to the fact that the CQDs surface can capture electrons, allowing the photogenerated electrons to be transferred from the Fe 0.1The conduction band of the Zr composite material migrates to the CQDs, where electron transfer occurs, further suppressing the recombination of photogenerated electron pairs.
[0044] Fig.10 The EIS analysis results of the samples are shown. 0.05 Fe 0.1 The Zr composite material has the highest separation efficiency of photogenerated charges. CQDs act as electron media to promote the transmission of photogenerated electrons between ZrO2 and Fe, improve the separation of carriers, effectively promote light-induced charge transfer, and help ROS to be rapidly generated in the initial reaction stage.
[0045] In summary, the present invention successfully prepared C with high efficiency photocatalytic performance. 0.05 Fe 0.1 The co-doping of Zr composite materials, Fe and CQDs can significantly improve the photocatalytic activity of ZrO2, reduce the band gap, promote the separation of carriers, inhibit the recombination of photogenerated electron pairs, reduce the charge transfer barrier, and prolong the lifetime of photogenerated carriers, thereby significantly improving the photocatalytic performance. The composite photocatalyst shows extremely high application prospects.
[0046] Example 2 In this example, the composite photocatalyst of iron-carbon modified zirconium oxide is applied to the degradation reaction of glyphosate, and the specific process is as follows: All experiments were conducted in 50 mL photodegradation tubes. A certain amount of composite material was added to a photodegradation tube containing 50 mL of a certain concentration of glyphosate solution. The solution was mixed evenly by ultrasonication for 5 min and then stirred in a photoreaction box for dark adsorption. Rapid sampling was performed 5, 25, and 45 min after the adsorption reaction began. After that, a 300 W ultraviolet lamp was turned on for photoreaction, and rapid sampling was performed 1, 5, 10, 30, 60, and 90 min after the photoreaction began. The glyphosate analysis method was based on the "Glyphosate Technical Drug" (GB12686-2017): First, prepare several 50 mL brown stoppered colorimetric tubes, add 0, 0.5, 1.0, 1.5, 2.0, and 2.5 mL of 20 mg·L -1 Glyphosate solution (prepared and used immediately). Then, add 7.5 mL of deionized water, 0.5 mL of 50% H2SO4 solution, and 0.5 mL of 1 mol·L -1 KBr solution and 1 mL 0.1 mol·L -1NaNO2 solution (prepared and used immediately), shake well and let stand for 20 minutes. After standing, use deionized water to make up the volume of the solution in each colorimetric tube to the scale line, shake well again, open the stopper and let stand for 15 minutes. Finally, use a UV spectrophotometer to measure the absorbance of each sample, use deionized water as a blank control, and use a 10 mm quartz cuvette to measure at a wavelength of 242 nm, and draw a standard curve.
[0047] The calculation formula is shown in equation (1-1): (1-1) Where A1 is the absorbance of the standard solution, A2 is the absorbance of the sample solution, m1 is the mass of the standard, m2 is the mass of the sample, and w is the mass fraction of glyphosate in the standard.
[0048] ①Comparison of different crystal forms of ZrO2 The effects of different crystal forms of zirconium on glyphosate degradation were compared. The experimental conditions were: glyphosate concentration was 20 mg·L -1 , dosage of different crystalline zirconium is 0.15 g·L -1 After 5 minutes of ultrasonic mixing, the materials were placed in a light reaction box for dark adsorption and stirring for 45 minutes. Then, a 300 W ultraviolet light was turned on for 90 minutes, and then samples were taken to determine the glyphosate concentration.
[0049] Depend on Fig.11 It can be seen that the removal rates of glyphosate by cubic ZrO2 (c-ZrO2), monoclinic / tetragonal mixed ZrO2 (m / t-ZrO2), monoclinic ZrO2 (m-ZrO2), tetragonal ZrO2 (t-ZrO2) and amorphous ZrO2 increase in turn, among which the removal efficiency of amorphous ZrO2 for glyphosate is much higher than that of other composite materials, with an adsorption rate of 74.3% and an adsorption / photocatalytic total degradation rate of 78.1%; while the total degradation rates of glyphosate by c, m / t, m and t crystal forms of ZrO2 are all lower than 50.0%. The possible reasons are as follows: compared with traditional crystalline materials, the disordered atomic structure of amorphous materials can improve the exposed surface and increase the density of surface active sites; and the large number of dangling bonds and abundant unsaturated coordination sites generated by the amorphous phase also provide a large number of adsorption sites for glyphosate, so amorphous materials are more likely to combine with glyphosate to form surface complexes. In crystalline materials, the periodic structure of the lattice constrains electrons, while the distortion-strain effect of amorphous materials causes the energy of the system to enter a metastable state, enhancing electron transfer within and between orbitals and improving the surface charge transfer of adsorbed molecules.
[0050] Therefore, amorphous ZrO2 is the best choice.
[0051] ②Comparison of iron doping amount The effect of the molar ratio of Fe3O4 to ZrO2 on the degradation performance of glyphosate in the synthesized composite material was investigated. When preparing the FeZr composite material, the molar ratio of Fe to Zr was set to 1:0, 0:1, 0.01:1, 0.05:1, 0.1:1, 0.2:1, 0.3:1, and 0.4:1, respectively.
[0052] Depend on Fig.12 It can be seen that with the increase of the proportion of Fe in the composite material, the adsorption rate of glyphosate by the prepared FeZr composite material tends to decrease, while the photocatalytic rate tends to increase first and then decrease. When the mass ratio of Fe to ZrO2 is 1:0 and 0:1, the adsorption rate of glyphosate is 14.9% and 74.4%, respectively, and the total adsorption / photocatalytic degradation rate is 29.7% and 78.1%, respectively, indicating that the adsorption capacity of pure Fe for glyphosate is weak, and the photocatalytic degradation capacity of ZrO2 alone for glyphosate is also limited. When the molar ratio of Fe to ZrO2 is 0.1:1, the degradation efficiency of glyphosate by the composite material is the highest (adsorption rate: 70.9%; total degradation rate: 86.8%). As the Fe dosage increased to 0.2:1, 0.3:1 and 0.4:1, the total degradation rate of glyphosate decreased to about 74.4%. The reason may be that doping a certain amount of Fe expanded the light absorption range and reduced the bandgap width; at the same time, Fe can improve the surface properties of ZrO2 and introduce defect sites OVs.
[0053] Therefore, the optimal molar ratio of Fe to ZrO2 is 0.1:1.
[0054] ③Comparison of different biomass CQDs Compared with Fe 0.1 Effect of CQDs prepared from Zr composites loaded with different nitrogen-containing biomass materials (soy dregs, peanut shells, pistachio shells, chicken manure, pig manure and soybean straw) on the adsorption / photocatalytic degradation performance of glyphosate.
[0055] Depend on Fig.13 It can be seen that the adsorption rates of glyphosate on bean dregs, peanut shells, pistachio shells, chicken manure, pig manure and soybean straw were 65.8%, 69.2%, 65.8%, 67.6%, 69.5% and 71.5%, respectively; the corresponding adsorption / photocatalytic degradation rates were 92.9%, 96.7%, 96.7%, 96.7%, 99.0% and 99.1%, respectively. The results verified the adsorption of nitrogen-containing CQDs on Fe 0.1 The modification of Zr composite materials successfully improved the photocatalytic activity of ZrO2. The possible reasons are as follows: (i) CQDs have a large specific surface area, which increases the Fe 0.1The contact area between Zr and glyphosate increases the active sites of the catalyst; (ii) the above biomass contains rich organic components and characteristic groups (-CH3, -CH2, OH, C=O, C-OH, O-CH3, etc.), which can react with Fe 0.1 Zr undergoes organic-inorganic hybridization, changing Fe 0.1 The electronic structure of Zr improves the electron conduction efficiency and inhibits the recombination of photogenerated carriers, thereby improving the photocatalytic performance. 0.1 Zr composite materials (CFe 0.1 Zr) has the best overall degradation efficiency for glyphosate.
[0056] Therefore, soybean straw is the best choice as the nitrogen-containing biomass material for preparing CQDs.
[0057] ④Comparison of CQDs doping amount The CQDs and Fe 0.1 Effect of Zr molar ratio on glyphosate degradation performance of synthesized composite materials. Preparation of CFe 0.1 When the Zr composite material is used, the CQDs and Fe 0.1 The molar ratios of Zr are 1:0, 0:1, 0.01:1, 0.03:1, 0.05:1, 0.1:1, and 0.15:1, respectively.
[0058] Depend on Fig.14 It can be seen that with the increase of CQDs doping amount, the prepared CFe 0.1 The adsorption of glyphosate by Zr composite materials and the total adsorption / photocatalytic degradation rate first increased and then decreased. 0.1 When the molar ratio of Zr composite materials was 1:0 and 0:1, the adsorption rates of glyphosate were 11.15% and 70.1%, respectively, and the total degradation rates were 18.59% and 86.50%, respectively, indicating that the adsorption and photodegradation efficiency of glyphosate by CQDs alone were poor. 0.1 When the molar ratio of Zr composite material is 0.05:1, the degradation efficiency of glyphosate by composite material is the highest (total degradation rate is 99.0%). When the dosage of CQDs is further increased to 0.1:1 and 0.15:1, the adsorption and photodegradation rate of glyphosate by composite material decrease. This may be because: (i) when the amount of CQDs added is too small, the improvement of glyphosate photodegradation efficiency is limited due to the relatively weak interfacial electron transfer ability; (ii) CQDs are weaker than Fe 0.1 The adsorption capacity of Zr composites for glyphosate is weak. Excessive doping with CQDs reduces the adsorption of glyphosate on the composites and prolongs the mass transfer process. Excessive CQDs may cover the Fe 0.1 The Zr surface causes the composite material to insufficiently utilize light and thus reduces the photodegradation efficiency.
[0059] Therefore, CQDs and Fe 0.1 The optimal molar ratio of Zr composite material is 0.05:1.
[0060] Example 3 This example is to evaluate C 0.05 Fe 0.1 The adsorption / photocatalytic degradation performance of the Zr composite material on glyphosate and the stability of the composite material were investigated by batch experiments. The basic experimental method was the same as that of Example 2.
[0061] ① Adsorption / photocatalytic degradation performance of glyphosate in different reaction systems To explore C 0.05 Fe 0.1 The adsorption and photolysis performance of glyphosate by each component in the Zr composite material were studied under the same conditions. 0.1 Zr, C 0.05 Zr, C 0.05 Fe 0.1 and C 0.05 Fe 0.1 Zr removal experiment on glyphosate.
[0062] like Fig.15 As shown, ZrO2, Fe, CQDs, C 0.05 Fe 0.1 , Fe 0.1 Zr, C 0.05 Zr and C 0.05 Fe 0.1 The adsorption efficiency of Zr on glyphosate in the dark was 74.3%, 0.0%, 0.0%, 0.0%, 70.1%, 72.6% and 71.1%, respectively; the total adsorption / photocatalytic removal efficiency was 78.1%, 3.4%, 3.5%, 10.4%, 86.8%, 83.3% and 99.0%, respectively. That is, the system containing ZrO2 has a strong adsorption effect on glyphosate, and Fe, CQDs and C 0.05 Fe 0.1 The adsorption and photocatalytic effect of glyphosate are relatively weak, while the degradation effect of glyphosate by the composite material after ZrO2 doped with Fe and CQDs is significantly improved. At the same time, the photocatalytic degradation process of glyphosate was fitted using a pseudo-first-order kinetic model. The K values of glyphosate removal by each system are C 0.05 Fe 0.1 Zr(0.0563 min −1 )>Fe 0.1 Zr(0.0111 min −1 )>C 0.05 Zr(0.0073 min−1 )>ZrO2(0.0023min −1 )>C 0.05 Fe 0.1 (0.0022 min −1 )>CQDs(0.0008 min −1 )>Fe(0.0006 min −1 ), further indicating that C 0.05 Fe 0.1 The Zr composite material showed excellent adsorption / photocatalytic synergistic degradation under ultraviolet light. That is, there is a strong interaction between ZrO2, Fe and CQDs after the composite, which can play a synergistic promotion effect, thereby improving C 0.05 Fe 0.1 The catalytic degradation performance of Zr. The reasons may be: (i) the strong adsorption of ZrO2 increases the contact between glyphosate and the catalytic active sites, shortens the transmission path of photogenerated electrons and holes, improves the charge transmission efficiency and the activity of the photocatalyst; (ii) the doped Fe reduces the band gap of ZrO2, extends the light response range, and further increases the OVs in the material, so that a new OVs energy level is added between CB and VB, and electrons are more easily excited from VB to OVs, which can greatly promote the separation of photogenerated electrons and holes; (iii) the doped CQDs can act as electron conductors and acceptors, reduce the charge transfer barrier, promote the directional transfer of electrons from ZrO2 to Fe, and further migrate electrons to the catalyst surface, inhibit the recombination of photogenerated electrons and holes, prolong the lifetime of interface carriers, and generate more active species, that is, Fe-CQDs construct synergistic active sites, further improving the photocatalytic activity of ZrO2.
[0063] ②C 0.05 Fe 0.1 Stable Zr composites The stability of photocatalysts during the reaction is one of the important indicators for evaluating their performance. Therefore, the C 0.05 Fe 0.1 Stability of Zr.
[0064] Depend on Fig.16 As shown in the figure, in the first experiment, about 71.0% of glyphosate was removed after 45 min of adsorption in the dark; and then almost 99.1% of glyphosate was removed after 90 min of reaction under UV light. 0.05 Fe 0.1Zr composites were used for cyclic experiments after desorption with NaOH. In the second to fifth experiments, the adsorption rates at 45 min were 70.5%, 69.5%, 68.8% and 67.1%, respectively, and the total degradation rates were 96.3%, 93.3%, 89.6% and 87.3%, respectively. The cyclic experimental results showed that C 0.05 Fe 0.1 The Zr composite material can maintain good stability during the adsorption and photocatalysis of glyphosate and can be reused.
[0065] In summary, the present application creatively invented a composite photocatalyst of iron-carbon modified zirconia, which utilizes the high chemical stability of ZrO2 and its high affinity for glyphosate. After loading Fe and CQDs on ZrO2 using a simple ultrasonic method, the stability of ZrO2 is retained while successfully extending the light response range, further increasing the OVs in the material, promoting the separation of photogenerated electrons and holes, and extending the lifetime of interface carriers, achieving the goals of synergistic adsorption / photocatalytic degradation of glyphosate and reusability, and expanding the application of ZrO2 in the field of photocatalytic degradation of organic pollutants.
[0066] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A composite photocatalyst of iron-carbon modified zirconium oxide, characterized in that: The composite photocatalyst includes an amorphous ZrO2 material and Fe3O4 and nanometer zero-dimensional carbon quantum dots (CQDs) doped in the material for modification; The composite photocatalyst material CFeZr is characterized in that, in the chemical composition, the molar ratio of C, Fe and Zr is x:y:z.
2. The composite photocatalyst according to claim 1, characterized in that: The molar ratio range of C, Fe and Zr is (0.05~0.1):(0.05~0.1):
1.
3. A method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide, characterized in that: The steps include: S1: adding zirconium n-butoxide to H2O2 solution, adding deionized water after stirring and continuing stirring, and finally subjecting the obtained mixed solution to hydrothermal reaction, cooling and drying, to obtain an amorphous ZrO2 material; S2: adding ZrO2 and Fe3O4 to a mixed solvent of deionized water and ethanol and ultrasonicating them, removing the supernatant by centrifugation after the ultrasonication, and drying the obtained precipitate in a vacuum oven to obtain a FeZr composite material; S3: CQDs were prepared using waste biomass nitrogen-containing carbon materials. FeZr and biomass were added to ethanol, the mixed solution was ultrasonically dispersed, and the suspension was dried to obtain a CFeZr composite material.
4. The method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide according to claim 3, characterized in that: In step 1, the mixture is stirred for 12 to 24 hours, and the temperature of the hydrothermal reaction is 160 to 180 °C for 1 to 2 hours.
5. The method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide according to claim 3, characterized in that: In the step 2, the molar ratio of Fe to Zr in the mixed solution is (0.05-0.1):1, and the ultrasonic time is 1-2 h.
6. The method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide according to claim 3, characterized in that: In step 3, the waste biomass is nitrogen-containing straw.
7. The method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide according to claim 3, characterized in that: In the step 3, the preparation of the waste biomass includes: pyrolyzing the waste biomass; the pyrolysis temperature is 400-500 °C, and the pyrolysis time is not less than 2 h.
8. The method for preparing a composite photocatalyst of iron-carbon modified zirconium oxide according to claim 3, characterized in that: In step 3, the molar ratio of Fe, Zr and biomass in the mixed solution is (0.05-0.1): (0.05-0.1): 1, and the ultrasonic time is 30-60 min.
9. The use of the composite photocatalyst of iron-carbon modified zirconium oxide according to any one of claims 4 to 8, characterized in that: The composite photocatalyst is used for photocatalytic degradation of glyphosate.
10. A composite photocatalyst of iron-carbon modified zirconium oxide, characterized in that: The active component of the composite photocatalyst includes the composite material of iron-carbon modified zirconia as described in any one of claims 4-8.
Citation Information
Cited By
Preparation method of zirconium-cobalt bimetal phthalocyanine and application of zirconium-cobalt bimetal phthalocyanine in degradation of glyphosate in water body
CN120094648A